„OGÓLNA TEORIA”, KEYNESIZM NIERÓWNOWAGI A WSPÓŁCZESNE PROGRAMY BADAWCZE - Bludnik, Izabela (Wydział Prawa i Administracji UAM, 2007)
According to the interpretation presented by disequilibrium Keynesianism, Keynes was not interested in the state o f equilibrium, but his main purpose was rejection of the perfect Walrasian model. Hence, unemployment and insufficient demand started to be perceived as disequilibrium phenomena. The main reason for that was attached to the problems of dissemination of credible information. Imperfect and costly knowledge in a large decentralised system leads to discrepancies between the effective and the notional demand. As a result, it is the quantities rather than prices that adjust. Focused studies o f solid microfoundations of the analysed aggregate problems gave an impulse to New Keynesianism, while imperfect information, coordination failures and quantity adjustments faced by individual agents became a cornerstone of the New Keynesian research agenda.
“GENERAL THEORY” , DISEQUILIBRIUM KEYNESIANISM, AND THE NEW RESEARCH AGENDA